Difference in the artefacts production and the performance of the metal artefact reduction (MAR) tool between the buccal and lingual cortical plates adjacent to zirconium dental implant - Nascimento, Eduarda Helena Leandro (Dentomaxillofac Radiol, 2019)
OBJECTIVES: To quantify the artefacts production and the performance of the metal artefact reduction (MAR) tool, enabled before or after the acquisition, in cortical plates (buccal and lingual) and other regions adjacent to zirconium implants. METHODS: Cone beam CT scans were acquired using the OP300 Maxio unit before (control group) and after (implant group) the insertion of a zirconium implant into the posterior region of a dry mandible. Three conditions of MAR tool were tested: “without MAR”, with “MAR activated after acquisition”, and with “MAR activated before acquisition”. The standard deviation (SD), contrast-to-noise ratio (CNR) and voxel values were calculated in the buccal and lingual cortical plates, medullary bone and water region, close to the implant. The structural bone analysis was performed in the medullary bone close to the implant. RESULTS: Overall, in control and implant groups, the lingual cortical had higher SD, lower CNR and lower voxel values than the buccal cortical, regardless of the MAR condition (p < 0.05). Implant caused higher SD values and lower voxel values in adjacent regions “without MAR” (p < 0.05). MAR activation decreased SD and changed voxel values when the implant was present, regardless of MAR activation mode (p < 0.05). The activation of MAR increased the trabecular thickness values for the implant group (p < 0.05). CONCLUSION: The expression of artefacts adjacent to zirconium implants is greater in the lingual than in the buccal cortical. The greater the expression of artefacts in this region, the greater the effectiveness of the MAR tool in homogenizing the grey values, regardless of the time of its activation.